2017
DOI: 10.5152/eurjrheum.2017.160073
|View full text |Cite
|
Sign up to set email alerts
|

Catastrophic antiphospholipid syndrome treated with rituximab: A case report

Abstract: Catastrophic antiphospholipid syndrome (CAPS) is a rare and fatal condition that is characterized by diffuse venous and/or arterial thromboembolism within a short period of time and histopathological confirmation of small-vessel occlusion in at least one organ or tissue in the presence of positive antiphospholipid antibodies. Here we report the case of a 19-year-old woman with CAPS. During the first week of her hospitalization, she was diagnosed with CAPS on the basis of skin necrosis, pulmonary artery thrombo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 5 publications
0
6
0
1
Order By: Relevance
“…However, the number of patients taking rituximab was too low to determine its effectiveness or safety profile 13. It is believed that rituximab reduces cytokine production by reducing B cells and minimises the systemic inflammatory response 14. Despite treatment with high dose steroid, intravenous immunoglobulin, plasma exchange and immunomodulators like rituximab, CAPS has shown to have high mortality that approaches 50%.…”
Section: Discussionmentioning
confidence: 99%
“…However, the number of patients taking rituximab was too low to determine its effectiveness or safety profile 13. It is believed that rituximab reduces cytokine production by reducing B cells and minimises the systemic inflammatory response 14. Despite treatment with high dose steroid, intravenous immunoglobulin, plasma exchange and immunomodulators like rituximab, CAPS has shown to have high mortality that approaches 50%.…”
Section: Discussionmentioning
confidence: 99%
“…Rituximab has also been used to treat CAPS with variable response [ 10 , 88 , 89 , 90 , 91 , 119 , 120 ]. For example, Rubenstein et al [ 89 ] reported a patient with CAPS resistant to treatment with heparin and methylprednisolone 1 mg/kg/day, successfully treated with rituximab 375 mg/m 2 once a week for four weeks [ 89 ].…”
Section: The Current Role Of Immunosuppressant Drugs In Antiphosphmentioning
confidence: 99%
“…Среди 20 пациентов, получавших лечение РТМ, выздоровление отмечено у 16 (80%), однако 4 пациента умерли. Сходные данные об эффективности РТМ у пациентов с катастрофическим АФС (первичном или в сочетании с СКВ) приводят другие исследователи [131,148,149,[194][195][196].…”
Section: антифосфолипидный синдромunclassified